2013
DOI: 10.1080/10615806.2013.810213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anxiety on the execution of police arrest and self-defense skills

Abstract: We investigated the effects of anxiety on the execution of police officers' arrest and self-defense skills. Police officers (n=13) performed three tasks in which they kicked, blocked, or restrained an opponent who attacked them with a rubber knife (low anxiety, LA) or a shock knife (high anxiety, HA) in a within-subject design. We analyzed performance (on a 5-point Likert scale), movement times, posture, and movement velocity and acceleration. Results revealed that performance was worse in the HA compared to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 20 publications
2
45
0
Order By: Relevance
“…The average anxiety scores (FIRST: M pre = 5.2, SD = 2.2, M post = 4.4, SD = 1.9; ASDS: M pre = 5.2, SD = 2.3, M post = 5.1, SD = 2.4) showed that anxiety scores were relatively high (see Renden et al 2014 for comparable scores in high anxiety scenarios), indicating that participants experienced the scenarios as threatening. Average anxiety scores ranged from 3.5 (SD = 2.0) in 'passive aggressive' to 6.3 (SD = 2.9) in 'handgun attack' .…”
Section: Anxietymentioning
confidence: 99%
See 3 more Smart Citations
“…The average anxiety scores (FIRST: M pre = 5.2, SD = 2.2, M post = 4.4, SD = 1.9; ASDS: M pre = 5.2, SD = 2.3, M post = 5.1, SD = 2.4) showed that anxiety scores were relatively high (see Renden et al 2014 for comparable scores in high anxiety scenarios), indicating that participants experienced the scenarios as threatening. Average anxiety scores ranged from 3.5 (SD = 2.0) in 'passive aggressive' to 6.3 (SD = 2.9) in 'handgun attack' .…”
Section: Anxietymentioning
confidence: 99%
“…Both scales have good psychometric properties (anxiety thermometer: test-retest correlations between .60 and .78, RSmE: test-retest correlations between .71 and .81) and were used in earlier ASDS experiments (e.g. Nieuwenhuys et al 2009;Renden et al 2014). …”
Section: Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, affective components influence the emotional state in which the defender has to perform (functionality), like anxiety caused by situational constraints creating pressure on the performer [Nieuwenhuys et al 2009;Renden et al 2014] or emotionladen situations [Headrick et al 2015]. This allows the performer to experience the emotions associated with the task and how this impacts their thoughts and action (e.g.…”
Section: Martial Arts Studiesmentioning
confidence: 99%